Does an emotion‐focused two‐chair dialogue add to the therapeutic effect of the empathic attunement to affect?. (27th September 2017) - Stiegler, Jan Reidar; Molde, Helge; Schanche, Elisabeth
Abstract: An increasing amount of research suggests that it is beneficial to work explicitly with emotions in psychotherapy. Emotion‐focused therapy (EFT) utilizes interventions that are thought to enhance the evocativeness of emotional processing and facilitate explorations of new meaning. The purpose of this study was to examine the effect of such an intervention on therapeutic outcome. The intervention, a two‐chair dialogue drawn from emotion‐focused therapy, was added to the treatment conditions that consisted of empathically following the clients' emotional processes. The treatment comprised 2 phases. Using a multiple baseline design, 21 self‐critical clients (15 women and 6 men) with clinically significant symptoms of depression and/or anxiety first received 5, 7, or 9 sessions of a baseline treatment focused on alliance building, empathic attunement to affect, and therapeutic presence and genuineness. A two‐chair dialogue intervention was then added for 5 sessions. The symptoms were measured before each session using Beck's Depression Inventory, Beck's Anxiety Index, and Forms of Self‐Criticizing/Attacking and Self‐Reassuring Scale. An analysis using Hierarchical Linear Modelling revealed that the phase with the two‐chair dialogue had a larger impact on symptoms of anxiety and depression when compared to the baseline phase. On BDI‐II, there was a greater impact on somatic‐affective components than cognitive components. Self‐criticism was reduced when we used time as a predictor for both phases but not significantly more after introducing the intervention. The results corroborate that the two‐chair dialogue intervention is associated with change beyond what is shown when relationship conditions alone are being provided. Implications and limitations are discussed.